2011
DOI: 10.1111/j.1464-0597.2011.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Fit of Political Skill to the Work Context: A Two‐Study Investigation

Abstract: A two-study investigation was designed to examine the role of job type (i.e. fit of political skill to work context) as a contextual moderator of the political skill-job performance relationship. Specifically, it was hypothesised that political skill operates most effectively in enterprising job contexts, and thus is most predictive of job performance in such contexts, but political skill would demonstrate no relationship with job performance in job contexts that did not emphasise interpersonal interaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 52 publications
1
64
0
4
Order By: Relevance
“…Furthermore, this is the first study to examine the moderating role of political skill in an R&D context and to establish its link to innovativeness and job performance. So far, political skill has been mostly used either within samples comprising individuals from different job groups or in contexts where social interactions are thought to be a key element of the occupational activities, such as sales representatives (Blickle et al., , ; Blickle, Froehlich, et al., ). While innovation and creativity in organizations are gaining in importance, understanding organizational innovation is important to the management of R&D professionals as well as other groups of employees who are increasingly expected to show innovativeness in the workplace (Scott and Bruce, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this is the first study to examine the moderating role of political skill in an R&D context and to establish its link to innovativeness and job performance. So far, political skill has been mostly used either within samples comprising individuals from different job groups or in contexts where social interactions are thought to be a key element of the occupational activities, such as sales representatives (Blickle et al., , ; Blickle, Froehlich, et al., ). While innovation and creativity in organizations are gaining in importance, understanding organizational innovation is important to the management of R&D professionals as well as other groups of employees who are increasingly expected to show innovativeness in the workplace (Scott and Bruce, ).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived leadership effectiveness was measured by follower assessments using the scale developed by Blickle et al () and used by Ewen et al (). The items were: How is this person (1) leading a group at work, (2) leading a business, (3) leading discussions, (4) advertising, (5) organizing meetings, (6) supervising others, (7) selling, (8) persuading others, (9) monitoring compliance, (10) bargaining, (11) speaking on behalf of a group, and (12) motivating others.…”
Section: Methodsmentioning
confidence: 99%
“…Persons high on political skill have a powerful ability to adapt their behavior to a variety of contexts (Ferris, Treadway, et al, 2005), and thus, are better able to meet these adaptive demands of a complex job. Moreover, two studies (i.e., Blickle, Kramer, et al, 2009; Blickle et al, ) that examined political skill's relationship with performance considered the occupational context, and the results from both indicated that political skill was a stronger predictor in complex occupations. Similarly, Sturman () demonstrated that in complex jobs, experience becomes a stronger predictor of performance over time, which indicates the importance of work‐related skills (e.g., political skill) in complex job contexts.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%